Pengaruh Kecerdasan Spiritual (SQ) dan Kecerdasan Emosional (EQ) Terhadap Motivasi Belajar Mahasiswa Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang - Dalinur M. Nur; Emi Puspita Dewi (Wardah, 2019)
Abstract: This study aims to determine (1) the influence of spiritual intelligence, and emotional intelligence together on the learning motivation of students in Da'wah and Communication Management of the Islamic State University of Raden Fatah Palembang, and (2) the influence of spiritual intelligence, and emotional intelligence partially towards the learning motivation of students of Da'wah and Communication Management of Da'wah Fatah Islamic University in Palembang. In this study the sample was 138 people. The research design used was multiple regression models. The variables used are three variables, namely the independent variable in the form of Spiritual Intelligence (X1), and Emotional Intelligence (X2), and the dependent variable, namely Learning Motivation (Y). The analytical tool used is multiple linear regression. Based on the results of the study that: (1) There was a positive and significant influence of spiritual intelligence, and emotional intelligence together on the learning motivation of students of Da'wah and Communication Management of the Islamic State University of Raden Fatah Palembang, and (2) there was influence positive and significant spiritual intelligence, and emotional intelligence partially towards the learning motivation of students in Da'wah and Communication Management of the Faculty of Da'wah and Raden Fatah's Islamic University Palembang. Keyworld: Spiritual Intelligence, emotional intelligence and learning motivation